The Upper Pliocene - Quaternary geological history of the Shirak Basin (NE Turkey and NW Armenia) and estimation of the Quaternary uplift of Lesser Caucasus - Trifonov, V. G.; Simakova, A. N.; Celik, H.; Tesakov, A. S.; Shalaeva, E. A.; Frolov, P. D.; Belyaeva, E., V (Pergamon-Elsevier Science Ltd, 2020)
Stratigraphy, structure, and tectonics of the Turkish part of the intermontane Shirak Basin and the adjacent Susuz Basin were studied based on methods of structural geology, geological and geomorphological correlation, paleontology, paleomagnetism, and archaeology. For the first time, the Pliocene-Quaternary stratigraphy and tectonics of the western Turkish and eastern Armenian parts of the Shirak Basin were correlated. Sedimentary cover of the western part of the basin consists of four units: the Lower Akchagylian (Piacenzian) marine deposits, Karakhach, Ani, and Arapi lacustrine-alluvial units. The Upper Pliocene age of the former formation in the Demirkent section is evidenced by normal palaeomagnetic signature and dinocysts of the Akchagylian aspect with some forms known to have a highest stratigraphic datum near the Pliocene Quaternary boundary. The age of the Karakhach unit is estimated at 1.9-1.7 Ma based on similar geomorphological position and composition with corresponding deposits in Armenia, normal polarity, and a record of the Early Palaeolithic artefact. The dating of the Ani unit to the Calabrian, and the Arapi unit to the lower Middle Pleistocene is evidenced by assemblages of molluscs and small mammals, Acheulian artefacts, palaeomagnetic data, and geomorphological position similar to the correlated sedimentary sequences in the Armenian part of the basin. The level of the Akchagylian brackish water basin at the Neogene Quaternary boundary (2.58 Ma) was close to the recent oceanic level. The recent altitude of the top of the Lower Akchagylian deposits in the Demirkent section is 1565 m. This defines the average rate of the Quaternary uplift in this part of Lesser Caucasus at 0.6 mm/year. The Shirak Basin is bounded and ruptured by fault and flexure-fault zones. Because of offsets on the Camuslu and Akhuryan zones, the central part of the northern Shirak Basin is subsided relative to the Demirkent section at 130-165 m. The movements in the Carcioglu zone caused a 100-120 m rise of the Ani unit surface in the Susuz Basin relative to the adjacent part of the Shirak Basin. The north-western border of the Susuz Basin is uplifted on the Sarikamis fault zone. Thus, the Quaternary uplift ranges near 0.6 +/- 0.1 mm/year. To the north of the Shirak Basin, in the Upper Akhuryan and Lori Basins and the Debed River valley, the rate of uplift during 0.65-0.6 Ma is estimated at about 1 mm/year and the adjacent Bazum and Javakheti Ridges rose more intensively. Therefore, the uplift could accelerate during the time interval of 0.65-0.6 Ma.
Keywords: Neotectonics; Stratigraphy; Dinocysts; Plio-pleistocene uplift; Turkey; Armenia